PENGARUH FAKTOR TEKNIKAL DAN FUNDAMENTAL TERHADAP HARGA SAHAM (STUDI KASUS PERUSAHAAN FOOD AND BEVERAGE DI BEI TAHUN 2019-2021) - M. WAHYULLAH; NI NYOMAN YULIATI; ANGGUN FARADILA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the significance of the stock price(t-1), stock trading volume, sales growth ratio, and profit growth ratio on the share price of F&B companies listed on the IDX for the 2019-2021 period. The sample of this study were 20 companies in accordance with the specified conditions, so that the observation data was 60. The analysis tool used multiple linear regression analysis. In order to get the best linear unbias estimation equation, it must meet the assumptions of normality, multicollinearity, autocorrelation and heteroscedasticity. The data will also be described through descriptive statistics. The model in this study fulfills the classical assumptions, so that its accuracy is guaranteed as a predictive and decision-making tool. Through the t test, only two variables have a significant effect (criterion Ha is accepted), namely the t-1 stock price and sales growth ratio. The resulting model is quite good for predicting the share price of F&B companies listed on the IDX, because it produces an adj R2 value of 86.80%. These findings indicate that investors in the IDX, especially in F&B companies, are classified as investors with an effort to take short-term profits, so they only pay attention to obtaining capital gains and guaranteeing high company activity (growth of sales ratio). An important suggestion in this study is that technical and fundamental approaches are still used for practical purposes, so it is necessary to study in depth.